Los valores como estrategia metodológica para concienciar sobre el cuidado y conservación del medio ambiente en los estudiantes del noveno año de la escuela de educación general básica José ingenieros - Torres Garcia, Juan Ramon (2018)
The research topic called VALUES AS A METHODOLOGICAL STRATEGY TO RAISE AWARENESS ABOUT THE CARE AND CONSERVATION OF THE ENVIRONMENT IN THE NINTH GRADE STUDENTS OF THE GENERAL BASIC EDUCATION SCHOOL JOSÉ INGENIEROS had as a general objective to determine the values as a methodological strategy to improve the protection of the The environment in the ninth grade students was descriptive of a pre-experimental type, using the methods of scientific, descriptive, analytical, deductive-inductive, synthetic and modeling observation; From the practical level, a questionnaire was used as a diagnostic to assess knowledge in a sample of 25 students. The most significant results obtained in the research is the lack of knowledge on issues related to the protection of the environment, so an alternative proposal based on 4 workshops was applied to the students of the José Ingenieros school in the city of Loja, of which it can be concluded after the application of the workshops that the researchers were sensitized to the environmental problem and incorporated new values such as: love, respect and responsibility changed their attitude to responsibly with our environment, so I recommend the teachers of The educational institution will continue with the proposal due to its effectiveness and the positive impact that the institution has caused, which was verified with the application of the pre-test post-test.